PERSONALITY STRUCTURE OF THE MAIN CHARACTER IN THE NOVEL THE GENTLEMAN SECRET BY AQUILEA: SIGMUND FREUD'S PERSONALITY THEORY - Nurhayati, Eni (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2024)
Personality is a dynamic organization of individual psychophysical systems that determine the behavior and thinking of individuals in a characteristic way. This study aims to describe the personality structure related to the id, ego, and superego of the main character in the novel “Aisyah Ibunda Kaum Mukmin” by Kamran Pasha. This study uses a discriptive qualitative method with the personality psychology approach of Sigmund Freud. Data collection techniques using note techniques. The data in this study were analyzed using heuristic and hermeneutic reading techniques. The results of this study indicate that there are three forms of the personality structure of the main character in Kamran Pasha’s novel “Aisyah Ibunda Kaum Mukmin”. The personality structure consists of: id, ego, and superego. The three personality structures dominate the main character. The id aspect always suppresses the ego so that its desires are fulfilled. On the other hand, the ego that acts as a personality arbiter does not have much power to suppress the id’s impulses, so Aisyah’s superego appears as a personality that appiles rules and tries to severely punish the ego’s mistakes in the form of regret and self correction